(untitled) (Journal of Forensic Medicine & Toxicology, 2013)
Present study was carried out in year 2009[01/01/ 2009 to 31/12/2009], during which total 923 medico legal autopsies were conducted at mortuary complex of Forensic Medicine Dept., Govt. Medical College and Sir T. General Hospital, Bhavnagar., out of which 142 autopsy cases of road traffic accident were studied in detail. A proforma bearing meticulous details of the individual like Age, Sex, Profile of victim, mode of event, details of vehicle involved, type of superficial and visceral injuries etc., was prepared. Master chart was prepared by classifying the data in proforma and interpreted further for discussion. Our study shows higher incidence of accidents in Age group of 21-30 years, Higher incidence was observed during working hours in 12.01 p.m. to 6.00 p.m, maximum victims were motorcyclist, followed by pedestrian, Head injury as a cause of death was observed in majority cases of road traffic accident. We have recommended certain preventive measures at the end of study.